Maintenance therapy for Crohn's disease. Issue 10 (October 2015) - Onal, Ibrahim K.; Beyazit, Yavuz; Altinbas, Akif; Kurt, Mevlut; Arhan, Mehmet
<x xml:space="preserve">Abstract</x> Crohn's disease (CD) is a chronic, persistent, and destructive disorder with different forms of clinical behavior and the disease appears to be progressive over the long term. Providing greater levels of mucosal healing and resolution of clinical symptoms may modify the course of CD. This will often necessitate long-term therapy with immunosuppressant or biological therapies. Both these classes of drugs have side-effects and the latter are also very expensive. Identification of a subgroup of patients with a low risk of relapse and validation of the relevant predictors in various cohort studies are the key points to be able to cease immunosuppressant and/or biological therapy in patients with CD in stable remission. The individual parameters 'mucosal healing', 'deep remission', 'fecal calprotectin', and 'C-reactive protein' or various combinations of these parameters seem to be promising tools for predicting successful withdrawal of maintenance therapy.